Impact of Educational Neuroscience Teacher Professional Development: Perceptions of School Personnel - Hachem, Maryam; Daignault, Katarina; Wilcox, Gabrielle (Frontiers in Education, 2022)
There has been an increased focus on the importance of educational cognitive neuroscience for teachers, yet the research on the outcomes of teacher training in this area are minimal. We created and implemented an Educational Neuroscience professional development (PD) delivered throughout the 2020-2021 school year. This study was co-designed between researchers and school district partners. Participants were school personnel from a high school in Western Canada consisting of approximately 1,400 students and 75 teachers. All participants in the PD, including teachers and school staff, were invited to participate in interviews about their experiences during the PD. Seven in-depth structured interviews were performed to understand participants’ experiences, their perceptions of the value of educational neuroscience, and how the PD impacted their teaching practice. Through inductive coding and thematic analysis, we found that the PD had a positive impact on participants and their students. The sessions primarily increased participants’ knowledge of neuroscience concepts and provided them with practical and useful applications that they were able to employ in their classrooms in areas related to lesson planning, assessment, and student engagement. Participants described the remarkable impact that increased neuroscience knowledge had on their relationships with students and on students’ own understandings of neuroscience concepts. Overall, these findings provide further evidence on the significance of infusing educational neuroscience in teacher PD and highlight the importance of collaborative programs between researchers and educators to bridge the research to practice gap.